Audience reactions to motor vehicle advertisements: a test of compliance with self-regulatory codes - Ouschan, Robyn; Fielder, Lynda; Donovan, Robert (University of Western Sydney, 2008)
Massive automobile advertising budgets suggest that consumers worldwide are exposed to a large number of motor vehicle advertising messages. This is of concern considering some motor vehicle advertisements may encourage unsafe driving practices. In fact, motor vehicle advertising contributes a significant proportion of all complaints received by the Advertising Standards Bureau (ASB). Further, it appears that many advertisements that may be non compliant appear to fall through the regulatory gaps. This paper presents a test of the Federal Chamber of Automotive Industries (FCAI) Voluntary Code of Practice for Motor Vehicle Advertising. It entailed assessing audience perceptions of the messages communicated in three advertisements which were the subject of complaint to the ASB, two of which (Ford, Jeep) were dismissed and the third (Mazda) upheld. Audience perceptions of the ads showed that the ASB were correct in upholding the Mazda complaint that the ad promoted speed and performance aspects of the vehicle. However, our results showed that the Ford and Jeep ads also communicated these messages to the same extent or greater. Our results also showed that the sort of driver behaviour portrayed in these ads is perceived by a majority of viewers as aggressive and risk-taking across all three ads. These results bring into question the approach the Australian Standards Bureau uses to determine whether an advertisement breaches the FCAI Voluntary Code of Practice for Motor Vehicle Advertising.